Vacuum stability and the dynamics of chiral symmetry breaking - Montero, J. C.; Natale, A. A.; Pleitez, V.; Novaes, S. F. (Elsevier, 1985)
An effective potential for composite operators is computed at stationary points with different ansatze for the fermion self-energy in abelian and non-abelian theories. The vacuum shows a chiral asymmetric phase with larger stability for a specific ansatz: the one which is harder at high momenta. © 1985.